2013
DOI: 10.1007/s12031-013-0078-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Genetic Polymorphism and Stroke Subtypes in Chinese

Abstract: In conclusion, we found that -1195G>A polymorphism and A-1195-G-765 haplotype of COX-2 were associated with susceptibility to ischemic stroke in a Chinese population. The effects were confined to SVO among the stroke subtypes rather than to LAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Figure 2 shows that a significantly larger proportion of Chinese patients with stroke and DM have lacunar stroke compared with non-Chinese patients, whereas non-Chinese patients have a significantly higher proportion of middle cerebral artery infarctions. This supports our original notion that Chinese patients may be especially vulnerable to SVD and is consistent with findings from a study conducted in Hong Kong indicating that SVD and hemorrhages are more likely than other stroke types (22). Figure 3 shows an analysis of the frequency of SVD versus large vessel disease in our cohorts and indicates the same difference, whereby SVD is more frequent in Chinese patients with stroke and DM than in non-Chinese patients with similar diagnoses.…”
Section: Discussionsupporting
confidence: 91%
“…Figure 2 shows that a significantly larger proportion of Chinese patients with stroke and DM have lacunar stroke compared with non-Chinese patients, whereas non-Chinese patients have a significantly higher proportion of middle cerebral artery infarctions. This supports our original notion that Chinese patients may be especially vulnerable to SVD and is consistent with findings from a study conducted in Hong Kong indicating that SVD and hemorrhages are more likely than other stroke types (22). Figure 3 shows an analysis of the frequency of SVD versus large vessel disease in our cohorts and indicates the same difference, whereby SVD is more frequent in Chinese patients with stroke and DM than in non-Chinese patients with similar diagnoses.…”
Section: Discussionsupporting
confidence: 91%
“…One of the research focuses is cyclooxygenase 2 (COX-2), a key enzyme in prostaglandin biosynthesis. A study showed that a COX-2 genetic polymorphism in the Chinese population may contribute to the risk of developing white matter lesions [10]. Our previous study also revealed that using COX-2 inhibitor can attenuate CSVD in an animal model [11].…”
Section: Introductionmentioning
confidence: 84%
“…It has been shown that the COX-2-765G>C polymorphism is a protective factor against ischemic stroke in Italians [34], but the association between COX-2-765G>C and ischemic stroke and leukoaraiosis could not be replicated in Chinese [27,38] and Koreans [39]. As for COX-2-8473T>C, Maguire et al [40] demonstrated a significant effect of the COX-2-8473T>C polymorphisms on ischemic stroke functional outcome in Australians, while no association between the COX-2-8473T>C polymorphisms and intracerebral hemorrhage was observed in Koreans [41].…”
Section: Plos Onementioning
confidence: 99%
“…Reportedly, the COX-2-8473 C>T polymorphism has an effect on COX-2 mRNA and protein levels [19], the COX-2-765 G>C polymorphism might modify COX-2 mRNA [20], and the COX-2-1759 G>A polymorphism can influence COX-2 activity [24]. In addition, these SNPs have been demonstrated to be associated with several diseases involving COX-2, including bronchial asthma [23], coronary artery disease [25], cerebral infarction [26], and stroke [27].…”
Section: Introductionmentioning
confidence: 99%